Using Intelligent Systems to Improve Case Flow in Court Systems - Martins, A. (Intelligent Systems Design and Applications, 2017)
Courts of Law often take so long to produce final decisions. The reasons why court cases do not flow faster have already been approached, but literature in scarce in exploring how to enhance that flow. This paper aims at identifying ways to make legal cases flow faster through the legal process and increase courts’ value proposition from a technological perspective. Research is based on a flow and value approach. Two procedures are compared, a national Civil Declarative Procedure and the European Small Claims Procedure. Court procedures are analyzed from the perspective of its process’ activities and human intervention. Findings point that delays of court cases occurs mainly due to direct human intervention, particularly from the judge the case is assigned to, and that the activities involved can be performed based on pre-defined rules. Recommendations are produced on how to improve court procedures’ customer value using intelligent systems.